2012
DOI: 10.1186/1742-4755-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Parent-young people communication about sexual and reproductive health in E/Wollega zone, West Ethiopia: Implications for interventions

Abstract: ObjectivesThis study aims at examining parent-young people communication about sexual and reproductive health related topics and factors associated with it from both young people’s and parents’ perspectives.MethodsA cross-sectional study was conducted among 2,269 young people aged 10–24 years in Nekemte town and semi urban areas, western Ethiopia. Chi-square and multivariate logistic regression analyses were conducted using SPSS for windows version 16. The qualitative data was coded, and categorized in to emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
83
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 14 publications
45
83
3
Order By: Relevance
“…This difference may be due to socio economic difference of the society. Majority (85.4%) of respondents reported that they had no any pocket money given to them but only (48.1%) of them had pocket money of less than 200 birr, The study done in Wolega (55%) of respondents had pocket money less than 200 birr [20]. This may be due to the socio economic and cultural difference of the society.…”
Section: Socio Demographic Characteristics Of Students and Parentsmentioning
confidence: 84%
See 2 more Smart Citations
“…This difference may be due to socio economic difference of the society. Majority (85.4%) of respondents reported that they had no any pocket money given to them but only (48.1%) of them had pocket money of less than 200 birr, The study done in Wolega (55%) of respondents had pocket money less than 200 birr [20]. This may be due to the socio economic and cultural difference of the society.…”
Section: Socio Demographic Characteristics Of Students and Parentsmentioning
confidence: 84%
“…Out of the total 103 respondents 65(63.1%) of them had discussed about contraceptive methods, the study done in south west Nigeria (70.5%) of respondents and study done in Mekele (35.3%) of respondents had discussed about contraceptive methods with their parents [41,43]. This difference may be due to cultural variation of the society, difference for the accessibility of information about SRH issues and variation of knowledge of students and parents about contraceptive, in our study from the total of 58 female participants who were discussed about SRH 41(70.7%) of them had discussed about menstruation with their parents, the study done in Wolega (10.4%) of female respondents had discussed about menstruation, study done in south west Nigeria (87.1%) of female respondents had discussed about menstruation [20,41]. This variation may be due cultural difference of the society and method of data collection of the study.…”
Section: Communication Of Students About Srh Issues With Their Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young women narrated how they hardly communicated with their parents about sexual matters except in the form of receiving warnings. 26 "Don't bring home a dikala [bastard child]" was something frequently said to young women.…”
Section: Contextualizing Infrequent and "Unplanned" Sexmentioning
confidence: 99%
“…It has been noted that sexual communication is predictive of condom use, and reported as a means to self-efficacy among heterosexuals [13,14]. Sexual behaviors of the young people is shaped and influenced by conversations and interactions with peers [1,2,11,[14][15][16][17][18]. Young people are more likely to talk openly with close friends.…”
mentioning
confidence: 99%